2005
DOI: 10.1093/sleep/28.6.728
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Occupational Stress to Insomnia and Short Sleep in Japanese Workers

Abstract: This study suggested that occupational stress is a possible risk factor for insomnia and short sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
73
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 48 publications
11
73
2
1
Order By: Relevance
“…Other research has not found such an association in terms of daytime sleepiness (Breslau et al, 1997) or the development of sleep problems (Linton, 2004). In studies that have considered psychosocial job stressors and shiftwork simultaneously, controlling for shiftwork did not reduce the associations between other stressors and sleep to non-significant levels (Frese and Harwich, 1984;Ota et al, 2005;Sekine et al, 2006;Utsugi et al, 2005), suggesting that shiftwork does not mediate the relationships between stressors and poor sleep quality. Although we did not have a direct measure of shiftwork, we conducted an additional analysis using a proxy measure of the percentage of workers in the respondent's occupation that worked non-standard hours, based on information from the US Bureau of Labor Statistics (2005; not shown but available from the authors).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Other research has not found such an association in terms of daytime sleepiness (Breslau et al, 1997) or the development of sleep problems (Linton, 2004). In studies that have considered psychosocial job stressors and shiftwork simultaneously, controlling for shiftwork did not reduce the associations between other stressors and sleep to non-significant levels (Frese and Harwich, 1984;Ota et al, 2005;Sekine et al, 2006;Utsugi et al, 2005), suggesting that shiftwork does not mediate the relationships between stressors and poor sleep quality. Although we did not have a direct measure of shiftwork, we conducted an additional analysis using a proxy measure of the percentage of workers in the respondent's occupation that worked non-standard hours, based on information from the US Bureau of Labor Statistics (2005; not shown but available from the authors).…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were reported by Pelfrene et al (2002) in a study of Belgian workers. Recent research in samples of Japanese workers has also suggested that job demands and job strain are associated with sleep related problems (Ota et al, 2005;Sekine et al, 2006;Utsugi et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study as well, those with high job demand appeared to experience insomnia 1.30 times more frequently than those with low job demand. Akerstedt et al 29) reported that high job demand caused sleep disorders in Swedish workers, and studies on Japanese workers using Karasek's DCM model also reported that job demand and job strain are related with sleep disorders including insomnia 13,14,30,31) . Nomura et al 32) also reported that the frequency of insomnia experience was only half in those whose job control was above average.…”
Section: Discussionmentioning
confidence: 99%
“…For example, shift work is a well-known occupational risk factor for insomnia, and there is emerging evidence that individuals with shift work are at higher risk for lack of sleep 7,11) . Job stress has also been suspected to be an occupational risk factor for insomnia with the evidence showing a significant relationship between job stresses and sleeping problems including insomnia [12][13][14] . Recent studies from Japan reported that the feeling useful to others in the workplace was negatively associated with sleep disturbance and workplace bullying mediated between job strain and sleep disturbance 15,16) .…”
mentioning
confidence: 99%